MCD (LOS MARCADORES DISCURSIVOS) The pragmatic analysis of discourse markers (The argumentative texts of the ABC newspaper as a model): El análisis pragmático de los marcadores discursivos (Los textos argumentativos del periódico ABC como modelo) (Journal of the College of Languages (JCL), 2023)
When writing a text, such as a newspaper article, various types of discourse markers are frequently used to group sentences into paragraphs and parts in order to establish a discourse with certain functions, such as coordination, orientation, emphasizing the concepts presented, etc. It should also be noted that this type of mark exists in both written and spoken language. Therefore, it is convenient to dedicate a chapter to these linguistic elements to clarify their use and their classification, which is mainly based on Jose Portolés (2001), as well as the main features, specifically their features (prosodic, morphological, semantic and pragmatic).ResumenAl redactar un texto، como un artículo de periódicos، se utilizan con frecuencia varios tipos de MCD (los marcadores discursivos) para agrupar las oraciones en párrafos y secciones con el fin de establecer un discurso con discuencia varios tipos de MCD (los marcadores discursivos) para agrupar las oraciones en párrafos y secciones con el fin de establecer un discurso con selectaro or funciones، com. المفاهيم الحالية ، وما إلى ذلك. Por tanto، conviene dedicar un capítulo a estos elementos lingüísticos para aclarar su uso y su clasificación que se basa Principmente en Portolés (2001)، ademas los rasgos Principales، en concreto sus rasgos (prosódicos، morfolótic yos). Palabras claves : los marcadores discursivos ، analisis pragmatico ، texto مناقشة